Smooth muscle proteins from Hirschsprung’s disease facilitates stem cell differentiation - Hagl, Cornelia Irene; Heumüller, Sabine; Wessel, Lucas; Schäfer, Karl Herbert (Pediatric surgery international, 2012)
Background and aims The transplantation of neural crest derived stem cells (NCSC’s) is a potent alternative for the treatment of Hirschsprung’s disease (HSCR). Cells to be transplanted should ﬁnd an appropriate microenvironment to survive and differentiate. To investigate the quality of this microenvironment, effects of HSCR-smooth-muscleprotein extracts upon NCSC’s were studied in vitro.